2020
DOI: 10.1002/jpen.2028
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Immunonutrition in Elderly Patients Undergoing Total Hip and Knee Arthroplasty: Impact on Postoperative Outcomes

Abstract: Background: Arthroplasties in elderly patients are surgeries performed to ensure their quality of life. Perioperative care with specific nutrients can improve nutrition status and metabolic response to orthopedic surgeries, such as total knee arthroplasty (TKA) and total hip arthroplasty (THA). Methods: Retrospective study with elderly patients divided into 2 groups: control and immunonutrition. The immunonutrition group was instructed to start oral intake of the nutrition supplement 5 days before and to resum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…It is worth noting that in stage II, when dose selection was guided by the calculation formula, the number of patients admitted to the ICU was 0, while the literature reported that the ICU transfer rate was about 7% in the elderly after surgery for hip fracture under general anesthesia. 28 Given that the median age of patients in this study was as high as 80 years, the prognostic advantage of reducing the rate of ICU admission may have been greater than expected. In addition to the above, there are some peculiarities in this study in terms of the trial protocol.…”
Section: Discussionmentioning
confidence: 86%
“…It is worth noting that in stage II, when dose selection was guided by the calculation formula, the number of patients admitted to the ICU was 0, while the literature reported that the ICU transfer rate was about 7% in the elderly after surgery for hip fracture under general anesthesia. 28 Given that the median age of patients in this study was as high as 80 years, the prognostic advantage of reducing the rate of ICU admission may have been greater than expected. In addition to the above, there are some peculiarities in this study in terms of the trial protocol.…”
Section: Discussionmentioning
confidence: 86%
“…It is also important to note that optimizing patients preoperatively may require a lower threshold to designate nutritional risk given the stressful nature of surgical intervention. Indeed, several investigations have suggested that perioperative nutritional supplementation, even for patients not at risk, is associated with reduced muscle atrophy and accelerated return of functional mobility post-TJA 12,[44][45][46][47][48] (Table V).…”
Section: Nutritional Screeningmentioning
confidence: 99%
“…Most preoperative nutritional supplements are taken orally, as patients unable to tolerate oral intake would be considered at high risk for malnutrition on the basis of screening and would not be appropriate candidates for TJA. Notably, in the literature, most studies providing interventional recommendations were limited in that differences in patients' baseline nutritional status were not delineated among the cohorts utilized 12,[44][45][46][47][48] . However, such investigations provide insight into the value of universal perioperative nutritional supplementation given the reported benefits, including reduced LOS, mitigated weakness, improved functional levels, and more favorable metabolic profiles 4,12 .…”
Section: Role-specific Intervention: Patient Optimization and Providi...mentioning
confidence: 99%
“…It is worth noting that patients undergoing TKA were primarily geriatric. An investigation showed that more than 80% of patients were 65 years or older 3 . Along with the accelerated aging population, the prevalence of TKA in the elderly is expected to increase.…”
Section: Introductionmentioning
confidence: 99%